A Multinodular Mass of Abdominal Splenosis: Case Report of Uncommon Images of a Rare Disease - Hiroyuki Matsubayashi; Etsuro Bando; Hiroyasu Kagawa; Keiko Sasaki; Hirotoshi Ishiwatari; Hiroyuki Ono (Diagnostics, 2019)
Splenosis is a rare disease which typically forms single or multiple round masses. A 45-year-old male was referred for investigation of an abdominal mass. He had a history of splenic injury from a traffic accident at age 19. Contrast-enhanced computed tomography showed a well-enhanced, multi-nodular mass lesion, 3.5 cm in size, located below the stomach. An endoscopic ultrasound-guided fine needle aspiration biopsy (EUS-FNAB) for the mass was inconclusive. A surgery was performed, and pathology of the resected mass confirmed splenosis. Clinicians must bear in mind the possibility of occurrence of splenosis after splenic trauma and its image variations.